Part 1
We have the following polynomials:
(3-6n5-8n4)
(-6n4-3n-8n5)
Subtracting the polynomials we have:
(3-6n5-8n4) - (- 6n4-3n-8n5)
n5 (-6 + 8) + n4 (-8 + 6) + 3n + 3
Rewriting:
2n5 - 2n4 + 3n + 3
Part 2
For this case we have the following polynomial:
4x2-2x-5 = 0
Using resolver we have:
x = (- b +/- root (b ^ 2 - 4 * a * c)) / (2 * a)
x = (- (- 2) +/- root ((- 2) ^ 2 - 4 * 4 * (- 5))) / (2 * 4)
x = (2 +/- root (4 + 80)) / (8)
x = (2 +/- root (84)) / (8)
x = (2 +/- root (4 * 21)) / (8)
x = (2 +/- 2raiz (21)) / (8)
x = (1 +/- root (21)) / (4)
The roots are:
x1 = (1 + root (21)) / (4)
x2 = (1 - root (21)) / (4)